Perceptibility of pitch changes in a tonal signal emitted by a moving source - Urszula JORASZ (Archives of Acoustics, 2016)
The starting point for the experimental research described here was a psychoacoustic analysis of the Doppler effect. The investigations were performed under laboratory conditions using an electronic model of a moving source. Data were obtained on the relationship between the sensations of pitch and loudness of a tonal signal under dynamic conditions.